Perancangan Sistem Akuntansi Aset Tetap Pada Zangkar Adventure Equipment - Ranti Fitriani Fauziah; Jouzar Farouq Ishak (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
In the rental activity, many obstacles occured for intance losing of documents, accumulating of data, doubling of related fungtions and poor internal control. The main purpose of designing a fixed assets accounting system is to know the existing procedures and overcome the weaknesses and obstacles that often occur. In this study the authors used a descriptive qualitative research type. In designing a flowchart and data flow diagrams that have gone through the analysis process of collecting company data and proposing solutions to solve problems and are expected to provide benefits in improving company performance and fulfilling elements of a good internal control system. The result of the analysis and the proposed improvements regarding the rental system are expected to minimize existing problems and can provide the information needed in making decisions and make it easier to achieve company goals.